Oligometastatic breast cancer: a case report and literature review - Ostapenko, Valerijus; Cicėnas, Saulius; Ostapenko, Andrejus; Briedienė, Rūta; Ostapenko, Edvinas (Lietuvos chirurgija, 2016)
Introduction Oligometastatic breast disease is a potentially curable state of distant cancer spread, but there is still no standard approach for treatment. The aim of this article is to present a clinical case of oligometastatic breast cancer and short data of the latest literature sources. Case report This case report presents 58 years old postmenopausal women diagnosed with oligometastatic breast carcinoma who underwent a successful simultaneous nipple-sparing mastectomy with sentinel node biopsy and right upper lobectomy in National Cancer Institute, Vilnius, Lithuania. Conclusions Multidisciplinary approach and modern imaging studies allows us to diagnose and successfully treat this rare pathological state. Scientific trials to delineate proper indications for oligometastatic breast disease are needed